Proposed guidelines for utilizing community learning resources in social studies instruction in secondary schools : a case study of Kampong Thom Province, Kingdom of Cambodia - Chantheng Meak (Chulalongkorn University, 2013)
Thesis (M.Ed.)--Chulalongkorn University, 2009